2022
DOI: 10.1289/isee.2022.p-0760
|View full text |Cite
|
Sign up to set email alerts
|

Historic redlining and the siting of oil and gas wells in the United States

Abstract: BACKGROUND:The presence of active or inactive (i.e., postproduction) oil and gas wells in neighborhoods may contribute to ongoing pollution. Racially discriminatory neighborhood security maps developed by the Home-Owners Loan Corporation (HOLC) in the 1930s may contribute to environmental exposure disparities. OBJECTIVE: To determine whether receiving worse HOLC grades was associated with exposure to more oil and gas wells. METHODS: We assessed exposure to oil and gas wells among HOLC-graded neighborhoods in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…[68][69][70][71] For example, two recent studies found a strong relationship between racism in the housing marking as reflected in historical designations of investment risk ("redlining") and siting of urban oil and gas wells and fossil fuel power plants. 72,73 Extraction sites in marginalized communities are also more likely to flare excess natural gas, particularly in areas where co-occurring oil resources are more economically viable. 74 Natural gas infrastructure, such as pipelines, compressor stations, and power plants, are often located in the middle of low-income neighborhoods.…”
Section: Environmental Justicementioning
confidence: 99%
“…[68][69][70][71] For example, two recent studies found a strong relationship between racism in the housing marking as reflected in historical designations of investment risk ("redlining") and siting of urban oil and gas wells and fossil fuel power plants. 72,73 Extraction sites in marginalized communities are also more likely to flare excess natural gas, particularly in areas where co-occurring oil resources are more economically viable. 74 Natural gas infrastructure, such as pipelines, compressor stations, and power plants, are often located in the middle of low-income neighborhoods.…”
Section: Environmental Justicementioning
confidence: 99%